EVALUASI PROGRAM BANTUAN BERAS MISKIN (RASKIN) PADA KELUARGA MISKIN DI KELURAHAN GUNUNG BALE KECAMATAN BANAWA KABUPATEN DONGGALA - Juniarti Juniarti (Katalogis, 2016)
This study aims to address the implementation and impact factors rice assistance program for poor families in the Gunung Bale village, Banawa District-Donggala Regency. This research is categorised as qualitative descriptive design by providing frequency distribution table. The results of interview are shown on the frequency tables. The population in this study consists of 120 heads of family. They were determined by census technique so that the sample in this study amounted to 120 respondents, while the informants who answered the interview were purposively determined by the Head of Village and Social Affairs Section as well as the representatives of the neighbourhood in the Village of Gunung Bale. The results show that the implementation of the rice assistance program for the Poor families in the Village of Mount Bale has not been effective. The reason for this is thatall of 6  measurement indicators of rice assistance program have not been fulfilled yet. There are only 2 indicators are run according to the general guidelines that Raskinindicators, such as, on time and administratione indicators. The impact factors of rice assistance program for poor families in Bale Mountain village include the right target indicators, the right amount, the right price and the right quality. However, this study found that the receipients of this program are not on target because the data are used in the program based onCentral Beareu Statistics without verification through Village consultation. In addition, the receipients claim that they received less than 15 kg of rice. Also, the price is not similar to the rice assistance program general guidelines. The quality is not meet with the standard because the quality of the rice have been decreased and therefore it is not sufficient to consume.